3D interconnected ultrathin cobalt selenide nanosheets as cathode materials for hybrid supercapacitors. (10th April 2018) - Zhu, Yirong; Huang, Zhaodong; Hu, Zhongliang; Xi, Liujiang; Ji, Xiaobo; Liu, Yong
Abstract: 3D interconnected ultrathin CoSe nanosheets are prepared via a hydrothermal synthesis method and utilized as superior battery-like electrode material for the first time. Due to the features of the unique 3D interconnected ultrathin nanosheets with a large BET specific surface area, superior mesoporous structure and good electrical conductivity, the as-resulted 3D interconnected ultrathin CoSe nanosheets manifests a high specific capacity of 70.6 mAh g −1  at 1 A g −1 and remarkable rate performance with 52.8% of capacity retention rate at 100 A g −1 compared with 1 A g −1 . Furthermore, a novel aqueous hybrid supercapacitor is assembled by employing 3D interconnected ultrathin CoSe nanosheets and activated carbon as the cathode and anode, respectively. The assembled hybrid device displays a specific energy of 18.6 Wh kg −1  at a specific power of 750 W kg −1 and outstanding cycling life with 95.4% of the initial capacity retention for 20000 cycles at 5 A g −1 . These results imply that the unique 3D interconnected ultrathin CoSe nanosheets can be considered as highly potential candidate electrode materials for hybrid supercapacitors. Graphical abstract: Highlights: 3D interconnected ultrathin CoSe nanosheets are prepared by hydrothermal method. Excellent electrochemical behaviors are obtained, especially the rate performance. Unique 3D interconnected ultrathin nanosheets gives good electrochemical performances. 3D ultrathin CoSe nanosheets are used as cathode materials for hybrid device. The hybrid device exhibits superior electrochemical properties.